Aplikasi Pemesanan Jadwal Main Vero Futsal Berbasis Web - Ahmad Suhendri; Marshal Ibrahim; Risman Muhamad Hafidz; Thoyyibah. T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In the process of compiling our proposal entitled "Ordering a Web-Based Vero Futsal Main Schedule" we have encountered various obstacles, but thanks to the moral and material support from various parties, we were finally able to complete this task, therefore through this opportunity we express our gratitude and appreciation highest appreciation to all related parties who have assisted in the completion of this task. This task is still far from perfection, therefore we expect all constructive criticism and suggestions from all parties for the sake of improvement in the next assignment. We hope that this work will be especially useful for us and for other readers in general.The conclusion of this research is that a futsal field reservation system has been created Web-based which can be used as a solution to solving internal problems Futsal field reservation. Based on the conclusions of this study, it is recommended: (1) The web-based futsal field ordering system that was built is very helpful for consumers to do the ordering process.(2) With this web-based futsal field booking system, consumers can order courts without having to come to the venue.(3) Can provide information on the playing schedule easily.